Monitoreo de plagas, enfermedades y malezas en el cultivo de anís en tres zonas productoras del NOA - Rios, Silvia Fernanda; Alemanno, Gabriela Alejandra; Romano Norri, Martín María; Saldaño, Rafael Bernardino (Asociación Argentina de Horticultura (ASAHo), 2024)
Poster